Merging supercritical carbon dioxide and organocatalysis for the precision and green synthesis of poly(lactide)-based (co)polymers. (October 2017) - Grignard, B.; De Winter, J.; Gerbaux, P.; Gilbert, B.; Jerome, C.; Detrembleur, C.
Graphical abstract: Highlights: Solvent-free organocatalyzed synthesis of polylactide-based (co)polymers is shown. Thiourea combined with tertiary amine is an efficient organocatalyst in scCO2 . scCO2 is a green medium for the precision synthesis of polylactides. Abstract: Well-defined poly(lactide)-based block copolymers were synthesized by a heterogeneous solvent and metal-free green approach by using organocatalysts in supercritical carbon dioxide (scCO2 ). We first report on the homopolymerization of bothl - andd, l -lactide by organocatalyzed Ring-Opening Polymerization (o-ROP) by using a bicomponent organocatalyst composed of a thiourea derivative and various tertiary amines as cocatalysts. Control over the molar mass and dispersity is achieved until high monomer conversion although the polylactides are insoluble in the polymerization medium. The precision synthesis of PLA-based block copolymers from various CO2 -phobic hydroxyl end-capped macroinitiators such as polyethylene glycol, polycaprolactone, polybutylene succinate and polyphosphoester was then reported. Merging scCO2 with this organocatalytic system provides therefore a unique tool for the design under solvent-free conditions of poly(lactide)-based block copolymers that are insoluble in scCO2 .